Application of POAC on Community-Based Urban Groundwater Management - Sahda Derana (Soegijapranata Catholic University, 2021)
Community-based water management is intended to manage natural assets and to meet the water needs of households in the community. The management by the community takes form of informal management that focuses on social interaction, social norms, and relationships between people in the community. Although it is informal, this form of organization needs to pay attention on aspects of formal management covering planning, organizing, actuating, and controlling (POAC). To find out how the application of POAC in community-based water management, the research conducted case study of two locations in Kedungmundu village, Semarang City, Central Java, Indonesia. This research found that the implementation of management in the community-based urban groundwater in both locations faced various kinds of problems: lack of understanding of the community on how to manage their assets properly, no clear purpose of their management, absence of independence oversight, and lack of good communication. The results can be the evaluations for the management in both locations and for developing knowledge and practical insight of POAC application on similar community-based urban groundwater management in different locations for them to become sustainable management.